2015
DOI: 10.1080/00380768.2014.992042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of agricultural wastes on the hydraulic properties of a loamy sand cropland in Turkey

Abstract: This study was carried out to determine the proper amount of application for manure (M), hazelnut husk (Corylus avellane L.) (HH), tobacco (Nicotiana tabacum L.) (TO) and tea (Camellia Sinensis (L.)) (TE) wastes based on hydraulic property improvement of a loamy sand cropland in Turkey. The effects of agricultural wastes on field capacity (FC), permanent wilting point (PWP), available water content (AWC), relative saturation (RS) and initial infiltration rate (IR) were determined for a loamy sand soil 7 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…The high SOM generally increased the aggregate stability and total porosity, reduced bulk density, and changed the pore-size distribution of the soil. In the same respect, several previous studies have reported a significant positive correlation between SOM and total porosity percentage [51,[78][79][80][81][82]. The Pearson s correlation in the present study reaffirmed this finding and it was found that the SOM exhibited a positive and high correlation with capillary percentage (r = 0.80) and total porosity percentage (r = 0.83) (Figure 1).…”
Section: Impacts Of Inm Treatments On Soil Physical Propertiessupporting
confidence: 90%
See 1 more Smart Citation
“…The high SOM generally increased the aggregate stability and total porosity, reduced bulk density, and changed the pore-size distribution of the soil. In the same respect, several previous studies have reported a significant positive correlation between SOM and total porosity percentage [51,[78][79][80][81][82]. The Pearson s correlation in the present study reaffirmed this finding and it was found that the SOM exhibited a positive and high correlation with capillary percentage (r = 0.80) and total porosity percentage (r = 0.83) (Figure 1).…”
Section: Impacts Of Inm Treatments On Soil Physical Propertiessupporting
confidence: 90%
“…Moreover, the SOM lowered soil compaction and soil bulk density, which results in an improved total soil porosity and permeability, and because of that, there was a close relationship between SOM and soil hydraulic properties [51]. In this respect, several studies have reported that there was a direct relationship between different soil hydraulic properties and the amount of organic compost applied [64,80,84]. In the present study, the treatments that resulted in an improved SOM, such as observed in T7, T8, and T9, they also exhibited an improved Another important soil physical property is hydraulic properties, such as hydraulic conductivity, WHC, and infiltration rate.…”
Section: Impacts Of Inm Treatments On Soil Physical Propertiesmentioning
confidence: 99%
“…Sainju et al (2002) and Villamil et al (2006) have determined higher organic matter content when cover crop roots decompose and when their above ground biomass is incorporated into the soil. Most studies determined that the amelioration of soil physical properties is largely based on increases of organic carbon in the soils (Gülser and Candemir, 2015). Previous studies conducted on same experimental plots with the similar treatments showed that soil organic matter increased by CCs (Wegner et al, 2015;Demir and Işık, 2020).…”
Section: Resultsmentioning
confidence: 98%
“…Agricultural residues used as soil amendments or fertilizers may represent an excellent recycling strategy [54]. They are important to improve soil physical (e.g., structure, infiltration rate, plant available water capacity), chemical (e.g., nutrient cycling, cation exchange capacity, soil reaction), and biological (e.g., SOC sequestration, microbial biomass C, activity, and species diversity of soil biota) properties as organic soil conditioners [55][56][57][58]. Cultivating crops that produce substantial amounts of residues can increase SOC in the soil profile, depending on the tillage practices used [29].…”
Section: The Use Of Agricultural Wastes In Soilsmentioning
confidence: 99%